Application of Fiqh Rules on the Intention of “AL-UMURU BIMAQASHIDIHA” in Islamic Family Law - Masduki, Masduki; Somawinata, Yusuf; Hidayat, Ahmad (Dinasti Research, 2025)
Islamic law is built on arguments and rules, both those originating from revelation and the ijtihad of scholars. Although a law is determined based on arguments or rules of ijtihad, in fact scholars base it on the arguments from the revelation. Qawa'id fiqh is the result of ijtihad of scholars in compromising the will of the law maker (ash-Syari') in the reality of human life. One of the main rules in Islamic law is the principle of alumuru bimaqshidiha, all actions depend on the intent and intention of the perpetrator. This rule is very important in every aspect of Islamic law, both worship and muamalat, including in Islamic Family law, both concerning marriage, divorce, wills and other contracts. So that all actions of a person will ultimately get according to what he intended.